2013
DOI: 10.1007/s10071-013-0688-x
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect and learning: exploring the “Eureka Effect” in dogs

Abstract: Animals may experience positive affective states in response to their own achievements. We investigated emotional responses to problem-solving in dogs, separating these from reactions to rewards per se using a yoked control design. We also questioned whether the intensity of reaction would vary with reward type. We examined the response (behavior and heart rate) of dogs as they learned to gain access to different rewards: (1) food (2) human contact, and (3) dog contact. Twelve beagles were assigned to matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
69
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 41 publications
1
69
0
4
Order By: Relevance
“…Taken together these results indicated that receiving food treats might not be sufficient per se to induce a long-term change in adult pet dogs' autonomic system and this could be due to a number of reasons: on one hand, differently from the two previous studies using food as a reward [43,47], we tested adult pet dogs living within the household and accustomed to receive palatable treats from the owner; this might have limited the positive valence of the food stimulus. On the other hand, in our study food was provided directly to the dogs, i.e.…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
See 4 more Smart Citations
“…Taken together these results indicated that receiving food treats might not be sufficient per se to induce a long-term change in adult pet dogs' autonomic system and this could be due to a number of reasons: on one hand, differently from the two previous studies using food as a reward [43,47], we tested adult pet dogs living within the household and accustomed to receive palatable treats from the owner; this might have limited the positive valence of the food stimulus. On the other hand, in our study food was provided directly to the dogs, i.e.…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
“…HRV could increase [63] or decrease [47] and therefore at the present stage of knowledge on dog emotional reaction is difficult to make a more precise hypotheses. Finally, if receiving treats induced in dogs a positive emotional state we should observe an increase in tail wagging [43].…”
Section: Accepted M Manuscriptmentioning
confidence: 92%
See 3 more Smart Citations